Analysis of survival in patients with brain metastases treated surgically: Impact of age, gender, oncologic status, chemotherapy, radiotherapy, number and localization of lesions, and primary cancer site - Rotta,José Marcus (2018)
SUMMARY OBJECTIVE To evaluate the survival of patients with brain metastases treated surgically according to the potentially involved factors. METHODS 71 patients treated surgically were analyzed with the diagnosis of brain metastases during the period from January 2011 to November 2014, totaling 47 months of follow-up. The Kaplan-Meier curve method was used for survival analysis. Results We evaluated 71 patients with brain metastases treated surgically, 44 female and 27 male, mean age of 60.1 years. According to the Karnofsky scale, 44 patients were classified with Karnofsky greater than or equal to 70 and 27 patients with Karnofsky inferior to 70. Lung was the primary site most commonly found. Death occurred in twenty patients (28%), and lung tumors were responsible for the most deaths. Twelve patients had supra and infratentorial metastases, fifty-nine only had supratentorial lesions, and lesions were multiple in twenty-eight patients and single in forty-three. Thirty patients were also treated with chemotherapy, eighteen with chemotherapy and radiation therapy, while only three received just radiotherapy. Survival analysis by Kaplan-Meier curve showed no statistical significance regarding age, histological type, location, Karnofsky, chemotherapy, and radiotherapy. There was statistical significance regarding gender. CONCLUSION The factors analyzed did not change survival rates, except for gender. This fact may probably be explained due to the systemic and diffuse behavior of cancer.